Partisipasi Masyarakat Dalam Meningkatkan Mutu Pendidikan Di SDN Sawunggaling I 382 Surabaya - Choirul Wayhudi; Ida lutfiyatul Jamilah; Aminatun Habibah (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2026)
Community participation in improving the quality of education is a community contribution in the form of community rights and obligations to contribute to the achievement of school goals in terms of improving school quality in order to produce quality graduates. The focus of research in this study 1) How is Community Participation in Improving the Quality of Education at SDN Sawunggaling I 382 Surabaya? 2) What is the form of education quality at SDN Sawunggaling I 382 Surabaya? 3) What are the supporting and inhibiting factors of Community Participation in improving the quality of education at SDN Sawunggaling I 382 Surabaya? The approach used in this study is a qualitative approach with the type of field research (Field Research). The technique for determining research subjects uses purposive techniques. Data collection techniques include observation, interviews, and documentation. While interactive data analysis by Miles, Huberman, and Saldana includes data collection, data condensation, data presentation, and conclusion drawing. Data validity testing uses source triangulation and technique triangulation. The results of this study are: 1) Forms of community participation in improving school quality at SDN Sawunggaling I 382 Surabaya, namely in the form of decision making, participation in implementation, participation in involving activities that provide benefits and participation in evaluation. 2) Supporting factors for community participation in improving quality at SDN Sawunggaling I 382 Surabaya are: good communication between parents and the community, parental awareness of the importance of education, availability of funds/parental donations to support school activities. While the inhibiting factors are: lack of understanding of parents regarding funding and management of program implementation funds, limited time for parents to supervise children's learning. 3) School efforts to overcome obstacles to community participation in improving the quality of education at SDN Sawunggaling I 382 Surabaya, namely: a) Carrying out good communication with the community. b) Providing motivation and inviting the community to have an important role in school planning. c) Providing knowledge to the community to remind their children to continue learning.